Reinventing Rice Breeding: One pipeline, two systems - CGIAR Research Program on Rice (2021)
In line with transition to dry direct-seeded rice as a method of crop establishment in wet season of 2021 (June- October) all yield trials have been established both under DSR and transplanted conditions. These steps will continue until full adoption of dry DSR into the breeding programs in coming years.